PENGARUH RADIASI JENIS LAMPU TERHADAP PERTUMBUHAN TANAMAN KACANG KEDELAI - Adhitya Agung Pribadi; Fianti Fianti; Upik Nurbaiti (Universitas Lambung Mangkurat, 2021)
The research under study has the aim of knowing (1). How the incandescent lamp affects. (2) How does the LED Light influence. (3) How does the fluorescent lamp affect. (4) How does the Lumment Lamp affect. Against the growth of soybean plants. This study uses technical analysis of data obtained from observations and measurements in observing the growth of soybean plants that lasts for 10 days. The conclusions resulting from the study indicate that 1). Incandescent lamps are able to have an influence on the growth of soybean plants even though they only produce stem shoots. 2) LED lights can have an effect on the growth of soybean plants even though they only produce stem shoots. 3) Flourescent lamp is able to influence the growth of soybean plants by producing roots, stems and leaves. 4) Incandescent lamps can have an influence on the growth of soybean plants by producing roots, stems and leaves.